Increased cell membrane arachidonic acid in experimental colorectal tumours. Issue 4 (April 1991) - Nicholson, M L; Neoptolemos, J P; Clayton, H A; Talbot, I C; Bell, P R
Abstract : Tumour cell membrane fatty acid composition was investigated using an animal model of colorectal carcinogenesis. Eighty six male Wistar rats were fed experimental diets containing either 5% saturated fat or 20% saturated fat. Colorectal tumours were induced by intraperitoneal injection of azoxymethane, and control rats received saline. Animals were killed at intervals up to 26 weeks after the last injection of carcinogen for histology and lipid analysis. Cell membrane fatty acids in colonic mucosa and colorectal tumours were determined by gas liquid chromatography. Animals fed the 20% fat diet developed more carcinomas (28 cancers in 14 rats) than those fed the 5% fat diet (14 cancers in 15 rats; chi 2 = 8.03, p = 0.0046) but they did not develop significantly more adenomas (28 and 24 respectively). Cell membrane fatty acid analysis showed a considerable increase in the content of arachidonic acid (20:4, n-6) in the tumours (mean (SEM) 11.7 (1.5)%) compared with colonic mucosa (4.2 (0.4)%; p less than 0.05). Dietary fatty acid composition was also found to influence the profile of fatty acids in the colonic mucosa. This study suggests that a high saturated fat diet promotes the malignant transformation of colorectal adenomas. The colorectal tumours were characterised by an increased cell membrane arachidonic acid, the precursor of putative cancer promoting prostaglandins.